2008
DOI: 10.1177/230949900801600108
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intra-Operative Metaphyseal Fractures with Prosthesis Size during Hemiarthroplasty of the Hip

Abstract: In elderly women with compromised bone quality, extra care is needed to achieve better fitting so as to avoid iatrogenic metaphyseal fractures. Under-sizing or cementing of the prosthesis is recommended when encountering difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The 7% incidence of IOF using a contemporary uncemented prosthesis design is comparable to that of others. 2 11 12 13 16) In comparison to previous studies using the JRI uncemented hydroxyapatite-coated prosthesis, 11 17 18) our IOF rate compares favourably. We attribute this to the longstanding experience and training in implanting the uncemented JRI HA prosthesis at our institution.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The 7% incidence of IOF using a contemporary uncemented prosthesis design is comparable to that of others. 2 11 12 13 16) In comparison to previous studies using the JRI uncemented hydroxyapatite-coated prosthesis, 11 17 18) our IOF rate compares favourably. We attribute this to the longstanding experience and training in implanting the uncemented JRI HA prosthesis at our institution.…”
Section: Discussioncontrasting
confidence: 51%
“…Most of the fractures in our cohort were around the femoral metaphysis (Vancouver A). Barlas et al, 17) in their cohort of 273 hip fractures treated using the JRI furlong H-A.C. prosthesis, demonstrated an IOF rate of 10.3%. Similarly, they also showed that Vancouver A was the only type of IOF sustained.…”
Section: Discussionmentioning
confidence: 95%
“…Further complications of bipolar hemiarthroplasty include intra-operative metaphyseal fractures reported in 10% of cases in a series of 273 patients with displaced femoral neck fractures, depending on extension of fracture dislocation [51]. The dislocation rate was reported to be 1.5% in a large series of 1934 hips [52], half of which redislocate after reduction.…”
Section: Resultsmentioning
confidence: 99%
“…16 In our study, the rate of intra-operative fracture in cementless bipolar hemiarthroplasty was 8.6%, which is comparable to 5.2% to 10% reported in other studies. 17,18 Greater trochanteric fractures occurred more commonly during proximal broaching or trial insertion. Surgeons should avoid excessive lateralisation of implants during broaching, reaming, and removal of the trial implant.…”
Section: Figurementioning
confidence: 99%